The Analysis Of Workload And Need Of Nurse With Wisn Method In Inpatient Room In Hospital X In Yogyakarta - Alon Ekawati (Universitas Muhammadiyah Yogyakarta, 2018)
The success of nursing service standard of inpatient care in Hospital X is supported by the availability of human resources. Therefore, the need analysis of performer nurses based on the workload should be done. The aim of the research was to find out the workload and the need for performer nurses using the WISN method. The research was qualitative in nature and the collecting technique of the number of the informant was with total sampling. The method of primary data collection was through observation and interview as well as secondary data like document study and the data of employee affair. The result of the research had WISN ration of 0.7. It showed that if the WISN ratio was <1, it meant that human resource in the unit has not met and did not correspond with the workload. Now, the number of human resource in the inpatient room of Al-Kausar was 15 nurses whereas the need according to the WISN method was 21 nurses. So, the total shortage was 6 nurses.